Characterization of Chemical Properties of Gandaria (Bouea macrophylla Griff) Restructuring Results Using Gelatin - Breemer, Rachel; Pattiruhu, Gysberth (Universitas Pattimura, 2023)
Fruits are one of the foodstuffs that have a lot of nutritional content. One of them is gandaria fruit (bouea macrophylla Griff). Gandaria is one of the perishable fruit commodities. To increase consumption and add value to gandaria fruit, it can be done by restructuring techniques. The purpose of this study was to examine the chemical characteristics of restructuring gandaria including water content, total acid, pH, vitamin C and ash content. The results showed that the interaction of agar and gandaria treatments had an effect on the water content. The single treatment of agar had no effect on the ash content. The best formulation from the results of this study was the treatment with 75% agar and 100 g of gandaria (A2B2).